2016
DOI: 10.1093/jtm/taw043
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of compliance rates with anti-vectorial protective measures during travel to regions with dengue or chikungunya activity, and regions endemic forPlasmodium falciparummalaria

Abstract: Poor AVPM compliance was observed in the overall cohort. Compliance with skin repellent use was associated with female gender, observing mosquitoes and travelling during the rainy season, and was not associated with the risk of malaria or chikungunya/dengue at the travel destination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Multiple traditional measures and strategies have been employed for dengue prevention and control, but most of these are compliance‐ and community involvement–dependent strategies which are hindered by poor compliance and absence of active local community involvement . Modern, integrated vector management approaches using novel biological control approaches such as paratransgenesis, sterile insect techniques, and production of genetically modified vectors, are urgently needed as well as innovative vaccine candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple traditional measures and strategies have been employed for dengue prevention and control, but most of these are compliance‐ and community involvement–dependent strategies which are hindered by poor compliance and absence of active local community involvement . Modern, integrated vector management approaches using novel biological control approaches such as paratransgenesis, sterile insect techniques, and production of genetically modified vectors, are urgently needed as well as innovative vaccine candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the relationships between health beliefs and sociodemographic factors. 16,39 These investigations were based on the premise that "Health decision-making is a process in which the individual moves through a series of stages, " such that subsequent behavior is dependent on the interaction at each of these stages. 20 Early evidence for the relationship between demographic factors, health beliefs, and health behavior was provided by the study of Kegeles et al 40 They reported that within all age, income, educational, and occupational groups, women who believed in the benefits of taking preventive action made the decision to take a Papanicolaou test for detecting cervical cancer more than women without those beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…40 After analyzing the findings of several studies on use of health services, Rosenstock 20 concluded that relatively higher educated individuals were more likely to use health services. Lalani et al 16 reported a significant association between the female gender and compliance with use of insect repellents. The current study found a significant association between higher levels of education and self-reported use of insect repellents for Chikungunya prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rationale: Compliance with personal protective measures such as insect repellents [20] are low [21]. Wolbachia -infected mosquitoes or genetically modified male mosquitoes appear promising [22,23], but their use remains controversial and large-scale implementations are unlikely in the near future.…”
Section: Research Areamentioning
confidence: 99%